Integrasi Taguchi Loss Function dengan Fuzzy Analytical Hierarchy Process dalam Pemilihan Pemasok - Ahmad S. Indrapriyatna; Yumi Meuthia; Dicky Fatrias; Monalisa Gusti (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2011)
One important issue in the line production is the selection of the company's best supplier. Various criteria should be considered for determining the best supplier. Answering to that challenge, we apply Taguchi loss function- Analytical Hierarchy Process Fuzzy-Linear Programming (Taguchi loss function-Fuzzy AHP) to find out the best supplier. Moreover, we also consider multiple criteria, i.e., goods’ completeness, quality, delivery, and quality loss in that analysis. By maximizing the suppliers’ performances based on each criterion and aggregated the suppliers’ performances based on the overall criteria, we selected the best one. Applying this method for selecting the best pressure gauge’s supplier in PT. Coca Cola Bottling Indonesia Central Sumatera (PT. CCBICS), we found out that among three suppliers, the second supplier is the best one.